Світлоклітинний рак нирки різних ступенів диференціації: особливості ультраструктури пухлинних клітин - Зербіно, Д.Д.; Федевич, С. В.; Ковалишин, В.І. (Онкологія, 2017)
Мета: проаналізували у порівняльному плані ультраструктурну організацію пухлинних клітин (ПК) світлоклітинного раку нирки (СКРН) різних ступенів диференціації. Об’єкт і методи: матеріалом слугували після операційні біоптати периферичної та центральної частин пухлин: високодиференційованого СКРН (G1) — 5; раку середнього ступеня диференціації (G2) — 5; раку низького ступеня диференціації (G3) — 6 випадків. Контроль: біоптати ниркової кори елімінованих нірок (їх частин та цілих органів) хворих на СКРН; біоптати ниркової кори статевозрілих білих щурів. Метод трансмісійної електронної мікроскопії. Результати: в альвеолах, тубулах і ацинусах СКРН різних ступенів диференціації містяться ПК високої, низької та середньої електронної щільності з переважанням останніх у СКРН G1. Контрольні дослідження дали можливість виявити, що ультраструктурна організація ПК середньої електронної щільності СКРН G1 є близькою до такої високодиференційованих епітеліальних клітин канальців проксимального відділу нефрона ниркової кори ссавців в нормі та високодиференційованих епітеліальних клітин канальців проксимального відділу нефрона ниркової кори хворих на СКРН G1. Висновки: ПК середньої електронної щільності пухлин високодиференційованого (G1) СКРН порівняно із клітинами пухлин середнього (G2) та низького (G3) ступенів диференціації СКРН мають найбільш «нормалізовану» ультраструктуру. Aim: is to reveal in comparative plan ultrastructural organization of tumor cells (TC) of clear cell renal cell carcinoma (CCRCC) of different grades of differentiation. Object and methods:material for conducting transmission electron microscopic researches was postoperative biopsies of peripheral and central parts of tumors in CCRCC at highly differentiated cancer (G1) — 5 cases; at an average grade of differentiation (G2) — 5 cases; at low grade of differentiation (G3) — 6 cases. The control studies: 1) the biopsies of renal cortex of eliminated parts of the kidney with tumor and the whole kidney with tumor in these patients in CCRCC; 2) biopsies of renal cortex of sexually mature white rats. Results: it was detected that the high, low and average electron density of the TC with the predominance of the last are present in alveoli, tubules and acini of different grades of differentiation at CCRCC in tumors of highly differentiated (G1) at CCRCC. The control studies made it possible to reveal that the ultrastructural organization of epithelial cells with an average electronic density of tumors with a high grade of differentiation (G1) at CCRCC is close to that of epithelial cells with a high grade of differentiation of proximal part of renal cortex of control mammals and epithelial cells of proximal part of renal cortex of tumors with a high grade of differentiation (G1) in patients at CCRCC. Conclusions: the ultrastructure of tumoral cells with an average electronic density of tumors with a high grade of differentiation (G1) at CCRCC is a more «normalized» in comparative plan than the same epithelial cells with the average (G2) and the low (G3) grades of differentiation at CCRCC.